EFFECTIVENESS OF INSTRUCTIONAL DESIGN FRAMEWORK BASED ON COGNITIVE LOAD THEORY FOR CLINICAL SKILLS TRAINING - Nourhan F. Wasfy; Rabab Abdel Raoof Abed; Enas Mohamed Gouda; Mona Sayed Ghaly; Yasser Mohamed El-Wazir (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2021)
Purpose: Cognitive load theory (CLT) is receiving increased recognition in medical education and it was cited as an important theoretical framework for simulation-based medical education. Simulated learning environments can place a high demand on the cognitive resources of the learners, hence, we aimed to design an instructional framework to optimise the total cognitive load imposed on the medical students during their clinical skills training in the clinical skills laboratory. Method: This study is a quasi-experimental post-test design. The sampling technique was purposive sampling, which included year 2 students at the Faculty of Medicine-Suez Canal University population. The study was conducted in the clinical skills and simulation laboratory. The intervention group received a developed instructional design framework based on CLT. The control group learned with the ordinary teaching method without any intervention. The cognitive load was measured using the Cognitive Load Inventory (CLI) immediately after the training session for both groups. Furthermore, students' achievement in the clinical skill laboratory was compared in both groups. Findings: The total cognitive load is lower in the group that received the developed instructional design than that of the control group, and this result was statistically significant. Also, the performance of the intervention group is higher than in the control group. Implications for research and practice: The developed instructional design framework is a potentially useful guide for managing students' cognitive load in the clinical skills training session.